Health equity in Nebraska: addressing disparities through place-based policy innovation - Yan, Changmin; Hughes, Michelle L.; Crawford, Lindsey B.; Cantu-Hines, Maria; George, Roopan Miriam; Dev, Dipti A.; Bashford, Gregory R. (Frontiers in Public Health, 2025)
This policy paper examines persistent health disparities in Nebraska, drawing on insights from a symposium that engaged more than 180 health professionals and organizational leaders statewide. Nebraska’s dual burden of rural provider shortages and urban socioeconomic inequities highlights the need for place-based policy solutions tailored to diverse regional drivers of health disparities—an approach that can be adapted by other states facing similar urban–rural divides. The paper urges Nebraska-focused public health policies with strategies other states can adapt. Key recommendations include expanding pediatric mental health services, implementing community-based interventions targeting social determinants of health, and increasing access to care through telehealth, and culturally and linguistically appropriate services. These approaches aim to advance equity in Nebraska and inform broader national efforts to reduce health disparities.